The Whole Ginkgo Resource: Flowers, Seeds, Leaves, Branches, and Trees—A Comprehensive Review of Their Active Ingredients, Pharmacology, and Applications - Wang, Yu‐Ying; Li, Rui‐Hong; Zhang, Guang‐Jie; Xia, Zi‐Ming; Li, Bin; Li, Min; Liu, Shu‐Chen (Chemistry & biodiversity, 2025)
Ginkgo biloba L. is a valuable tree species with high medicinal value in China. First recorded in Sheng Nong's herbal classic, the medicinal citation of its leaves and seeds began in the Song Dynasty. The medicinal value of G. biloba leaves has been widely studied for a long time, but relatively few studies have been conducted on other parts of G. biloba , such as its flowers and shoots, and there is a great need for a systematic review of their active ingredients and potential applications. The aim of this study is to comprehensively review the bioactivities of all parts of G. biloba , especially the research progress of G. biloba flowers and shoots. In addition, we will compare the new findings on ginkgo leaves and seeds to reveal the differences in their biological activities. We will review the chemical composition, pharmacological effects of these parts, and their potential applications in traditional medicine and modern drug development to fill the gaps in the existing literature. The contribution of this study is to provide new perspectives on the comprehensive use of ginkgo by highlighting the potential value of understudied parts of ginkgo flowers and branches. In addition, we summarize the latest research results on ginkgo leaves and seeds, which will provide a reference for research in related fields and promote the comprehensive development and utilization of ginkgo resources.